Barriers to clinical governance administration from point of view of managers and nurses - Mohsen Hojjat; Leila Mosalanejad; Maryam Charkhandaz; Elham Pabarja; Maryam Ehsani; Sepideh Mohammadi (Journal of Holistic Nursing and Midwifery)
Abstract